Nanostructure and Magnetic Field Ordering in Aqueous Fe3O4 Ferrofluids: A Small-Angle Neutron Scattering Study - A. Taufiq; S Sunaryono; N. Hidayat; E.G.R Putra; A. Okazawa; I. Watanabe; N. Kojima; S. Pratapa; D. Darminto (PPIKSN-BATAN, 2019)
Despite the importance of reducing production costs, investigating the hierarchical nanostructure and magnetic field ordering of Fe3O4 ferrofluids is also important to improve its application performance. Therefore, we proposed an inexpensive synthesis method in producing the Fe3O4 ferrofluids and investigated their detailed nanostructure as the effect of liquid carrier composition as well as their magnetic field ordering. In the present work, the Fe3O4 ferrofluids were successfully prepared through a coprecipitation route using a central precursor of natural Fe3O4 from iron sand. The nanostructural behaviors of the Fe3O4 ferrofluids, as the effects of the dilution of the Fe3O4 particles with H2O as a carrier liquid, were examined using a small-angle neutron spectrometer (SANS). The Fe3O4 nanopowders were also prepared for comparison. A single lognormal spherical distribution and a mass fractal model were applied to fit the neutron scattering data of the Fe3O4 ferrofluids. The increasing carrier liquid composition of the fluids during dilution process was able to reduce the fractal dimension and led to a shorter length of aggregation chains. However, it did not change the size of the primary particles or building block (approximately 3.8 nm) of the Fe3O4 particles. The neutron scattering of the Fe3O4 ferrofluids under an external magnetic field in the range of 0 to 1 T exhibited in a standard way of anisotropic phenomenon originating from the nanostructural ordering of the Fe3O4 particles. On the other hand, the Fe3O4 powders did not show anisotropic scattering under an external field in the same range. Furthermore, the magnetization curve of the Fe3O4 ferrofluids and nanopowders exhibited a proper superparamagnetic character at room temperature with the respective saturation magnetization of 4.4 emu/g and 34.7 emu/g.